Layanan Informasi Pembayaran Biaya Kuliah Berbasis SMS Interaktif Pada Sekolah Tinggi XYZ - Fransiska Prihatini Sihotang; Fithri Selva Jumeilah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2018)
Sekolah Tinggi XYZ is one of the college that already use e-learning. This system used by lecturers, students, and administrators. Lecturers and students use the system to support the learning and teaching process. Administrators use it to submit information related to academics such as lecture schedules, exam schedules, payment announcements, and more. Every semester, the administrator will announce the payment information of the Biaya Pengembangan Pendidikan (BPP) and the Satuan Kredit Semester (SKS) fee in accordance with the predefined schedule. The announcement was only up to the students and not yet reached the parents. Until now parents of students are still not familiar with the use of the internet so they can not access e-learning website. Therefore, there are still many students who are late in making payments. Late payment may cause the student to pay a penaltyor postpone the college. To prevent this, an information system is created to disseminate payment schedule information via SMS gateway. The system will be built using Gammu as the SMS gateway server and using the Ruby on rails framework. With this system the payment schedule information will arrive directly to the student's parents. If parents wants to ask about the payment schedule, parents simply send SMS in accordance with the format that has been determined.